A Facial Chuna Manual Therapy for Peripheral Facial Nerve Palsy - Yu-Kyeong Park; Cho In Lee; Jung Hee Lee; Hyun-Jong Lee; Yun-kyu Lee; Jung-Chul Seo; Jae Soo Kim (MEDrang Inc., 2019)
The purpose of this study was to investigate useful manual therapy techniques for peripheral facial nerve palsy and to propose guidelines to be applied for current manual therapy techniques. Several databases were searched to find manual therapies for facial palsy. These therapies included cervical, and temporomandibular joint chuna manual therapy, proprioceptive neuromuscular facilitation, neuromuscular re-education, facial exercise, and mime therapy. Both cervical, and temporomandibular joint chuna manual therapy release nerve compression, helping blood circulation and nerve conduction. Proprioceptive neuromuscular facilitation uses irradiation, bilateral activation, and eccentric facilitation to improve muscle power and symmetry. Neuromuscular re-education, as a retraining tool for facial movement patterns, enhances neuromuscular feedback. Facial exercise helps the patient continuously move and massage facial muscle themselves. Mime therapy aims to develop a conscious connection between the use of certain muscles and facial expressions. The use of facial chuna manual therapy for peripheral facial nerve palsy can stimulate the proprioceptive neuromuscular receptors in the face. Peripheral facial nerve palsy has 4 phases; progress phase, plateau phase, recovery phase, and sequelae phase. Each phase needs different treatments which include relaxation, assistance, resistance, origin-insertion extension, and nerve pathway expansion.